Data on a highly stable electrocatalyst of NiCoPt/Graphene-dot nanosponge for efficient hydrogen evolution reaction - Ngoc-Anh Nguyen; Yousuf Ali; Van-Toan Nguyen; Oleksii Omelianovych; Liudmila L. Larina; Ho-Suk Choi (Data in Brief, 2020)
The data presented in this article are related to the research article entitled “NiCoPt/Graphene-dot Nanosponge as a Highly Stable Electrocatalyst for Efficient Hydrogen Evolution Reaction in Acidic Electrolyte (N.-A. Nguyen et al., 2020) [1]. This article reports a simple method to synthesize NiCoPt/Graphene-dot as an electrocatalyst with low Pt loading but high hydrogen evolution reaction (HER) performance. The morphology of NiCoPt/Graphene-dot was analyzed by scanning electron microscopy (SEM) and high-resolution transmission electron microscopy (HRTEM) techniques. The structural and chemical properties of NiCoPt/Graphene-dot were investigated by using X-ray Powder Diffraction (XRD) and X-ray photoelectron spectroscopy (XPS) techniques.